2004
DOI: 10.1177/0148558x0401900303
|View full text |Cite
|
Sign up to set email alerts
|

Does Capacity Utilization Affect the “Stickiness” of Cost?

Abstract: the 2000 MAR conference, and the anonymous reviewer for comments. This paper was previously titled "On the Behavior of Labor Cost in Therapy Clinics."1. Other research examining the stickiness of costs include Subramaniam and Weidenmier (2002) and Wiersma (2002).2. We define a large change as any change greater than 3 percent. Approximately 75 percent of all changes were less than +. 7 percent, reducing concerns that observations lie outside of the relevant range.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
136
0
11

Year Published

2011
2011
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 196 publications
(154 citation statements)
references
References 4 publications
7
136
0
11
Order By: Relevance
“…I have the following predictions for equation (5). Consistent with the underlying premise of the sticky cost literature as proposed by ABJ, I predict that β 2 will be negative.…”
Section: Modelsupporting
confidence: 62%
See 1 more Smart Citation
“…I have the following predictions for equation (5). Consistent with the underlying premise of the sticky cost literature as proposed by ABJ, I predict that β 2 will be negative.…”
Section: Modelsupporting
confidence: 62%
“…Subramanian et al [4] extend this study and determine that the observed asymmetric adjustment of current SGA and current CGS only holds for large changes in current sales revenues. Balakrishnan et al [5] employ private data from physical therapy clinics to show that stickiness is influenced by the extent to which capacity constraints bind, whereas Balakrishnan et al [6], using department-level data from hospitals, find that cost stickiness is more strongly observable with respect to an organization's core competency. Calleja et al [7] investigate cost stickiness in an international setting and find results supportive of the existing literature.…”
Section: Introductionmentioning
confidence: 99%
“…Recent studies, however, provide evidence that costs increase more when sales rise than they decrease when sales fall by an equivalent amount, i.e., costs are sticky (Anderson, Banker, and Janakiraman [2003], Balakrishnan, Petersen, and Soderstrom [2004], Calleja, Steliaros, and Thomas [2006], , Banker, Byzalov, Ciftci and Mashruwala [2012], Banker, Basu, Byzalov and Chen [2012], Chen, Lu, and Sougiannis [2012], Kama and Weiss [2013]). Again, suppose actual sales exceed sales forecast by $100 in a favorable scenario, and sales are below sales forecast by $100 in an unfavorable scenario.…”
mentioning
confidence: 99%
“…My paper provides evidence that SGA costs behave differently for government contractors. Balakrishnan, Petersen, and Soderstrom (2004) provided evidence that the magnitude of the change matters. They showed that very large changes in costs lead to greater responsiveness (less stickiness) than smaller changes, and argued that transaction costs will dampen or remove small changes, but not affect larger changes.…”
Section: Acquisition Research Program Graduate School Of Business and Pmentioning
confidence: 99%